Protótipo de baixo custo para contagem de sementes - (:unkn) unknown (Universidade Federal do Pampa, 2016)
The seed accountant, both the bench and coupled to precision agricultural machines, has been widely used in agriculture to optimize the uptime and quality of work. This equipment is commonly found in the market with high prices hindering its acquisition by researchers and producers. The aim of this study was to develop and evaluate a low-cost prototype for grain count / seed laboratory bench. The assembly of the prototype was performed with a metering mechanism, an electric motor, a perforated disk with ramp, an Arduino Uno, a light dependent resistor and a light emitting diode. For tests with the prototype was used a completely randomized design (CRD) in a two-way factorial scheme composed of three groups defined according to the number of seeds (500, 1000 and 1500 seeds tested), three delivery rates 17, 21 and 32 seeds s-¹, with 40 repetitions. The prototype performance was evaluated in the seed counts at different speeds. The prototype of the bench accountant presented moderate variability in the number of seeds counted in the nine tests and high precision in seed count at speeds 17 and 21 s-¹ to 1500 seeds tested. Therefore, the prototype can be built and used as a low-cost tool to increase operational efficiency, especially in research.
Keywords: Contadora; Arduino; Grãos; Sementes; Embarcado; Accountant; Grains; Seeds; Onboard; CNPQ::CIENCIAS EXATAS E DA TERRA